2018
DOI: 10.1029/2018gl078208
|View full text |Cite
|
Sign up to set email alerts
|

Intense Storms Increase the Stability of Tidal Bays

Abstract: Coastal bays and, specifically, back‐barrier tidal basins host productive ecosystems, coastal communities, and critical infrastructure. As sea level continues to rise and tropical cyclones increase in intensity, these coastal systems are increasingly at risk. Developing a sediment budget is imperative to understanding how storm events affect the system's resilience, where net import of sediment indicates growth and resilience against sea level rise, and net export of sediment indicates deterioration. Using hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
41
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 50 publications
3
41
0
Order By: Relevance
“…Our model shows how greater waves cause more erosion; however, this trend is not followed by the 0.7 m wave height, as it mainly causes deposition enriching in the marsh (Figure 7). Treating wave heights equal to 0.7 m as a storm-level [15], our results are in agreement with Castagno et al (2018) [48] who demonstrated, using Delft3D, that extreme events are likely to enrich coastal wetlands with more sediments.…”
Section: Discussionsupporting
confidence: 91%
“…Our model shows how greater waves cause more erosion; however, this trend is not followed by the 0.7 m wave height, as it mainly causes deposition enriching in the marsh (Figure 7). Treating wave heights equal to 0.7 m as a storm-level [15], our results are in agreement with Castagno et al (2018) [48] who demonstrated, using Delft3D, that extreme events are likely to enrich coastal wetlands with more sediments.…”
Section: Discussionsupporting
confidence: 91%
“…Despite this hypothesis, high marshes/scrub‐shrubs in both Youngs and Coquille, which experience RSLR rates of 0.3 ± 1.1 and −1.4 ± 0.9 mm yr −1 , respectively, are accreting apparently as a result of high annual average suspended sediment loads relative to estuary area. One possible explanation for continued sediment accumulation under these RSLR conditions, which requires further investigation along the Oregon coast, is that storms and other episodic, high‐water events (e.g., exceptionally high tides) may play an important role in controlling long‐term accretion, as others have observed (e.g., Cahoon, ; Castagno et al, ; Goodbred & Hine, ; Reed, ; Turner et al, ; Tweel & Turner, ) and as some are incorporating into morphodynamic models (Schuerch et al, ). Models of tidal wetland morphodynamics thus require better integration with data collected from field observations and experiments, especially in locations that have high capacity to expand our limits of understanding (Wiberg et al, ), such as those that exhibit relative sea level fall and highly episodic sediment fluxes.…”
Section: Discussionmentioning
confidence: 97%
“…Several studies have already demonstrated the ability of these natural solutions to efficiently attenuate storm surge, wave energy, and current velocities (Costanza et al, 2008;Garzon et al, 2019;Glass et al, 2017;Maza et al, 2015;Mendez & Losada, 2004;Möller et al, 2014;Möller & Spencer, 2002;Nepf, 2004;Resio & Westerink, 2008). Furthermore, these ecosystems continuously provide (not only during storm events) many cobenefits in addition to wave protection services, including water quality improvements, sediment budget, carbon sequestration and storage, fishery habitat, and opportunities for tourism, recreation, education, and research (Barbier et al, 2011;Castagno et al, 2018;Donatelli et al, 2018;Sutton-Grier et al, 2015). Another highly important coastal protection service of these ecosystems is the capacity of accreting vertically and maintaining shallow water depths under certain sea level rise rates (D'Alpaos et al, 2011;Kirwan et al, 2010;Temmerman et al, 2013).…”
Section: Introductionmentioning
confidence: 99%